PENENTUAN KLORIN BEBAS PADA INDIRECT COOLING WATER - M.Taufik Eka Prasada (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2018)
Analysis of free chlorine for ten days of indirect oleo chemical cooling water sample has been carried out. Analysis of free chlorine using a colorimetric instrument based on the occurrence of color after using DPD powder. The concentration level of the color of the sample on the colorimeter showed the level of chlorine. The results of research conducted for 10 days showed that the free chlorine content in indirect cooling water samples were 0.28-0.42 ppm. Chlorine levels obtained in accordance with the recommended quality standard 0.3-0.5 ppm.